WORK-FAMILY CONFLICT AND EMPLOYEE PERFORMANCE IN GHANA’S BANKING SECTOR - Morrison, Dorothy A.; Mensah, John Victor; Kpakpo, Gloria Naa Adorkor; Asante, Claudia (International Journal of Research -GRANTHAALAYAH, 2020)
Studies indicate that in recent times, many working adults have combined family and work roles but they find it difficult to effectively execute their duties. This is due to the fact that these roles are incompatible, and therefore cause work-family conflict which has adverse concerns for both employees and organizations. This study therefore examined effects of work-family conflict on job performance in a selected bank in Ghana. It is a cross-sectional study and it employed the quantitative research method. Simple random and stratified sampling techniques were used to sample 100 respondents and both primary and secondary data were used. The findings revealed that family demand, long working hours and heavy workload were among the reasons for work-family conflict. Flexible time schedule, supervisory support, supportive work environment, and formulation of family friendly policies such as child care services were strategies the bank used to minimise work-family conflict. A significantly negative correlation was established between work-family conflict and job performance showing that high levels of work-family conflict in employees leads to lower job performance. It was recommended that other banks without work-family conflict strategies should emulate the best practices of the study bank to help enhance the performance of their employees.